Nellore cattle (Bos indicus) and ticks within the Brazilian Pantanal: ecological relationships - Ramos, Vanessa N.; Piovezan, Ubiratan; Franco, Ana Helena A.; Rodrigues, Vinicius S.; Nava, Santiago; Szabó, Matías P.J. (2018)
Pantanal is a huge floodplain mostly in Brazil, and its main economic activity is extensive cattle raising, in farms characterized by an extremely wildlife-rich environment. We herein describe tick infestations of cattle and of the natural environment in Pantanal of Nhecolândia in Brazil, at areas with and without cattle during both dry and wet seasons. Environmental sampling resulted in three tick species: Amblyomma sculptum (423 nymphs and 518 adults), Amblyomma parvum (7 nymphs and 129 adults), Amblyomma ovale (3 adults) as well as three clusters and two individuals of Amblyomma sp. larvae. A significantly higher number of adult A. sculptum ticks was found in areas with cattle in the wet season. From 106 examinations of bovines 1710 ticks from three species were collected: Rhipicephalus microplus (55.7 % of the total), A. sculptum (38 %) and A. parvum (4.1 %), as well as 32 Amblyomma sp. larvae. A significant similarity was found between Amblyomma tick fauna from environment and on cattle during both seasons. All A. sculptum females on bovines were flat whereas many of A. parvum females and A. sculptum nymphs were engorging. Although R. microplus was the most abundant tick species on cattle, overall highest tick prevalence on bovines in the dry season was of A. sculptum nymphs. Lack of R. microplus in environmental sampling, relationship between cattle and increase in adult A. sculptum numbers in the environment as well as suitability of bovine for the various tick species are discussed.